Endoparasites of Wild Rodents in Southeastern Iran - Mehdi Nateghpour; Afsaneh Motevalli-Haghi; Kamran Akbarzadeh; AmirAhmad Akhavan; Mehdi Mohebali; Iraj Mobedi; Leila Farivar (Tehran University of Medical Sciences, 2015)
Background: This study was aimed to collect wild rodents for endoparasites determination in some parts of Sistan and Baluchistan Province, southeastern Iran nearby Pakistan and Afghanistan countries. Methods: A total of 100 wild rodents were captured alive with cage traps. Various samples were collected from blood and feces, also impression smear prepared from different organs. The samples were prepared by formalin-ether or stained with Giemsa, after that were examined under microscope. Results: All the caught rodents (47 Tatera indica, 44 Meriones hurriana, 5 Gerbilus nanus and 4 Meriones libycus) were studied for endoparasites emphasizing to their zoonotic aspects. Endoparasites including Spirurida, Hymenolepis diminuta, Hymenolepis nana feraterna, Trichuris trichiura, Skerjabino taenia, Trichostrongylus spp, Entamoeba muris, Chilomastix mesnili and Leishmania spp were parasitologically identified. Conclusion: Among 9 genera or species of the identified parasites at least 5 of them have zoonotic and public health importance.